The Unique Molecular and Cellular Microenvironment of Ovarian Cancer - Worzfeld, Thomas; Pogge von Strandmann, Elke; Huber, Magdalena; Adhikary, Till; Wagner, Uwe; Reinartz, Silke; Müller, Rolf (Frontiers in Oncology, 2017)
The reciprocal interplay of cancer cells and host cells is an indispensable perquisite for tumor growth and progression. Cells of both the innate and adaptive immune system, in particular tumor-associated macrophages (TAMs) and T cells, as well as cancer-associated fibroblasts enter into a malicious liaison with tumor cells to create a tumor promoting and immunosuppressive tumor microenvironment (TME). Ovarian cancer, the most lethal of all gynecological malignancies, is characterized by a unique TME that enables specific and efficient metastatic routes, impairs immune surveillance and mediates therapy resistance. A characteristic feature of the ovarian cancer TME is the role of resident host cells, in particular activated mesothelial cells, which line the peritoneal cavity in huge numbers, as well as adipocytes of the omentum, the preferred site of metastatic lesions. Another crucial factor is the peritoneal fluid, which enables the transcoelomic spread of tumor cells to other pelvic and peritoneal organs, and occurs at more advanced stages as a malignancy-associated effusion. This ascites is rich in tumor-promoting soluble factors, extracellular vesicles, detached cancer cells as well as large numbers of T cells, TAMs and other host cells, which cooperate with resident host cells to support tumor progression and immune evasion. In this review we summarize and discuss our current knowledge of the cellular and molecular interactions that govern this interplay with a focus on signaling networks formed by cytokines, lipids and extracellular vesicles, the pathophysiologial roles of TAMs and T cells, the mechanism of transcoelomic metastasis and the cell type selective processing of signals from the TME.